Identification and Analysis of the Cluster Structure of a Territory and its Impact on Regional Development: An example of Russia - KUDRYAVTSEVA, Tatiana; OLANIYI, Eunice Omolola (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
Identification, development, and management of the cluster structure of territories is an important factor of economic growth. The purpose of this study is to determine the cluster structure of Russian regions and assess the impact of these cluster specialization on the size of gross regional product (GRP). For this purpose, the methodology of the European Cluster Observatory was used and the following indicators were calculated: ‘Location quotient’, ‘Cluster size’, and ‘Cluster focus’ for 37 clusters in 83 regions of the Russian Federation within the period from 2009 to 2018. The calculation was performed using the developed automated database ‘Clusters of Russian regions’. Based on the results obtained, the cluster specialization was determined and hypotheses were tested on the presence of positive externalities, i.e. on the existence of a positive correlation between the cluster specialization of regions and the size of their GRP from 2011 to 2015. Thus, the authors conclude that the increased specialization of Russian regions lled to positive agglomeration effects - externalities. The proposed toolkit can serve as a reference for the development and justification of the state industrial cluster policy.